THE OPTIMALISASI PROGRAM KAMIS BERBUDAYA SEBAGAI UPAYA PENGUATAN DAN PEMBENTUKAN KARAKTER MURID DI SEKOLAH DASAR - Dwi Susanti, Meiga; Siti Mas’ula; Riska Pristiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Kamis Berbudaya program as an effort to strengthen and build students’ character in elementary schools. This research used a qualitative descriptive approach conducted at SDN Bulupasar, Kediri Regency. Data were collected through interviews, observations, and documentation involving teachers and students. The results showed that the Kamis Berbudaya program was implemented routinely through the use of regional languages, traditional clothing, and learning activities integrated with local culture. The program positively contributed to strengthening students’ character values, including discipline, responsibility, politeness, cooperation, respect, and social awareness. In addition, the program fostered students’ pride and love for local culture amidst the influence of globalization. However, several obstacles were found, such as students’ limited understanding of cultural values and the lack of variation in activities. Therefore, schools need to develop more interactive and engaging cultural activities to optimize character education based on local wisdom. The study concludes that the Kamis Berbudaya program can become an effective strategy for strengthening character education while preserving local culture in elementary schools.